Geografia de paisagem e perfil sanitário de bovinos curraleiro pé-duro criados nos biomas Cerrado e Caatinga - Lobo, Joyce Rodrigues (2018)
Multivariate statistical analysis was used for environmental groupings in Cerrado and Caatinga evaluating the relationship between positive serological prevalences for brucellosis, bovine viral diarrhea (BVD), infectious bovine rhinotracheitis (IBR), leptospirosis, enzootic bovine leukosis (EBL), neosporosis and toxoplasmosis in bovine Curraleiro Pé-Duro, associated with socioeconomic data of the municipalities. Serological results were obtained from the Pro-Centro-Oeste Network database; socioeconomic variables of IBGE and environmental data of the Laboratory of Image Processing and Geoprocessing of UFG and National Institute of Meteorology, in two periods 2006 and 2011. Environmental variables were grouped, later was performed discriminant analysis and canonical correlation. In 2006, cluster 1 was located in the Cerrado-Amazonian transition area and were associated the prevalences of brucellosis, leptospirosis, EBL, IBR and BVD; Cluster 2 was characterized by vegetation typical of Cerrado and was related the prevalence of neosporosis and toxoplasmosis; Cluster 3 was differentiated by water stress and presented the intermediate values of prevalence; Cluster 4 was characterized by areas for environmental protection of the native vegetation; and cluster 5 constituted an anthropogenic environment in the Cerrado. In 2011, cluster 1 was characterized by Cerrado regions rich in natural vegetation and Caatinga, warmer, lower rainfall and low altitudes were associated with the prevalences of LEB, IBR and BVD; Cluster 2 in dry regions associated with the prevalence of neosporosis; Cluster 3 Cerrado antropizado with more hot and humid climate, higher rainfall at high altitudes related to the prevalence of leptospirosis and brucellosis, in dairy cattle. Evaluation of the landscape in the prevalence of bovine diseases reflects historical and socioeconomic aspects of agriculture.